Adaptation of Millennial Optimization in Organizations - Gunawan, Wawan; Wicaksono, Soetam Rizky; Rusmawati, Retno Danu (Universitas Muhammadiyah Ponorogo, 2022)
The book of Managing Millennials as a whole is not arranged like a textbook that is heavy to read and study. The sentences arranged in it seem straightforward and effective and encourage readers persuasively to be able to understand millennials from a different point of view. The adaptation tips and recipes presented also have the impression of being very practical and easy to implement in a corporate and organizational environment.In the present, this book is still very relevant because millennials still dominate the employment today. In addition, the generation after millennials, namely those born above 2000, the way of handling is also still relatively the same as millennials themselves. So that managers and leaders of the organization are still recommended to read this book.The author of this book who is a military veteran but has an MBA education background, and has experience as a consultant in various companies in which there are elements of the millennial generation, tends to choose sentences with a predominance of command words that arouse the spirit of the reader. So for readers who come from among practitioners, this book is very suitable and light enough to be read repeatedly before being practiced to the real world. But for readers from academics, this book can be a short and concise reference alternative for teaching or for students who are doing research.